Relationship Between Curative Effect and Serum Inflammatory Factors Level in Male Patients With First-Episode Schizophrenia Treated With Olanzapine - Ma, Jun; Zhang, Yanting; Huang, Zhuowei; Liu, Xuebing; Lv, Luxian; Li, Yi (Frontiers in Psychiatry, 2021)
Schizophrenia is generally considered to be a central inflammatory disease. Inflammatory cytokines play a very critical role in the pathogenesis and treatment of schizophrenia. However, in the actual clinical practice, there is still a lack of confirmed biological indicators that can be used to evaluate the therapeutic effect of antipsychotics. In this study, 82 patients with first‐episode schizophrenia and 30 healthy controls were included. The Positive and Negative Syndrome Scale (PANSS) scores were evaluated and the serum levels of high‐sensitivity C‐reactive protein (hs‐CRP), interleukin 1β (IL‐1β), interleukin 6 (IL‐6), interleukin 17 (IL‐17), and transforming growth factor β1 (TGF‐β1) were detected, both at baseline and four weeks later. The patients were divided into two groups, the effective group and ineffective group, according to the reduction rate of PANSS. In the case group, the baseline levels of the five inflammatory factors were significantly higher in the case group as compared to the control group (P = 0.00, 0.00, 0.00, 0.00, and 0.00, respectively). Post‐treatment, the serum levels for IL‐1β, IL‐6, and IL‐17 were significantly higher in the effective group than the ineffective group (P = 0.00, 0.00, and 0.01, respectively). For every increase in the amount of IL‐1β, the risk of ineffectiveness increased by 7% (OR = 0.93[0.86–1.00]; P = 0.04), whereas for every increase in the amount of IL‐17, the risk of ineffectiveness increased by 5% (OR = 0.95[0.90–0.99]; P = 0.03). The results of the study showed the levels of inflammatory factors in patients with different therapeutic effects were different, and the changes in the amounts of IL‐1β and IL‐17 acted as predictors of poor efficacy.